'Parity with all nations': The 'coolie' trade and the quest for recognition by China and Japan. (19th December 2021) - Le Moli, Ginevra
Abstract: This article explores the quest for sovereign equality by China and Japan as it unfolded in a specific historical moment, the third quarter of the nineteenth century. It does so by focusing on the debate around the 'coolie trade', i.e., the traffic of Chinese indentured labourers, which offered an opportunity for non-Western countries such as China and Japan to position themselves with respect to Western conceptions of 'modernity' or 'civilization' and thereby advance their quest for 'parity with all nations'. Through a study of the Maria Luz case, decided in the early 1870s by Czar Alexander II and drafted by de Martens, the article sheds light on the different approaches of Japan and China with respect to international law at this critical historical juncture. Specifically, it shows that, although the coolie trade mostly affected China, it was Japan who first managed to reap a parity dividend by firmly condemning the practice, whereas China's action was steered by the circumstances. Eventually, however, China's growing interest in Chinese populations abroad paved the way for the establishment of its first permanent diplomatic representations overseas. For both countries, the events encapsulated by the Maria Luz case unveil an important, yet overlooked, moment in their quest for parity with all nations and, more generally, in their engagement with international law.